2021
DOI: 10.1007/s00018-021-03971-y
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and beta myosin isoforms and human atrial and ventricular contraction

Abstract: Human atrial and ventricular contractions have distinct mechanical characteristics including speed of contraction, volume of blood delivered and the range of pressure generated. Notably, the ventricle expresses predominantly β-cardiac myosin while the atrium expresses mostly the α-isoform. In recent years exploration of the properties of pure α- & β-myosin isoforms have been possible in solution, in isolated myocytes and myofibrils. This allows us to consider the extent to which the atrial vs ventricular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 211 publications
(333 reference statements)
0
24
0
Order By: Relevance
“…We consider that the differential effect of MgADP on the leftward shift of pCa 50 between PLV and PLA results from a difference in the apparent binding affinity of MgADP to ventricular myosin vs. atrial myosin. It has indeed been reported that the equilibrium constant of the ADP-release during the cross-bridge cycling is higher for atrial myosin than ventricular myosin ( Wang et al, 2013 ; Walklate et al, 2021 ), thereby decreasing the apparent affinity of exogenously added MgADP.…”
Section: Discussionmentioning
confidence: 98%
“…We consider that the differential effect of MgADP on the leftward shift of pCa 50 between PLV and PLA results from a difference in the apparent binding affinity of MgADP to ventricular myosin vs. atrial myosin. It has indeed been reported that the equilibrium constant of the ADP-release during the cross-bridge cycling is higher for atrial myosin than ventricular myosin ( Wang et al, 2013 ; Walklate et al, 2021 ), thereby decreasing the apparent affinity of exogenously added MgADP.…”
Section: Discussionmentioning
confidence: 98%
“…There are two isoforms of myosin II heavy chains, the α and β isoforms, which have differential ATPase activity and are differentially expressed. Within the heart, the β-isoform is predominantly expressed in the ventricle, while the α-isoform is mainly found in the atrium ( Walklate et al, 2021 ).…”
Section: Single-molecule Studies Of Cardiovascular Diseasesmentioning
confidence: 99%
“…For example, the y 24 ion corresponding to C-terminal MLC-2v matched closely to the theoretical isotopic distribution for each cardiac chamber, and the experimentally-determined mass matches the theoretical mass with sub-ppm accuracy, indicating agreement with previously reported MLC-2v sequence ( Figure S15A ). Due to considerable sequence heterogeneity between MLC-2v and MLC-2a, 27 the observed fragment ions overwhelmingly indicate the presence of MLC-2v in the atrial chambers and do not match with a truncated or alternatively-spliced MLC-2a isoform. LC-MS/MS revealed key fragment ions matching to the reported sequence of MLC-2a, such as the y 25 ion shown across left and right atrial tissues ( Figure S15B ).…”
Section: Resultsmentioning
confidence: 95%